(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Psidium guajava L. has long been used in traditional medicine for managing infectious diseases. However, there is limited scientific data on its antifungal potential and safety. This study investigated phytochemical composition, acute oral toxicity, and antifungal efficacy of stem bark extracts of P. guajava against Candida albicans isolated from patients with oral thrush. The stem bark was extracted using cold maceration with water and ethanol. Standard qualitative phytochemical screening was conducted. Acute toxicity testing followed OECD guideline 423 using mice at doses up to 4000 mg/kg. Antifungal activity was assessed using the disc diffusion method, while MIC and MFC were determined using broth microdilution. Data were analyzed using one-way ANOVA at a 95% confidence level. Both extracts contained phenols, tannins, terpenoids, flavonoids, alkaloids, and glycosides, while saponins were present only in the aqueous extract. No mortality or observable signs of toxicity were recorded up to 4000 mg/kg, indicating a wide safety margin (LD₅₀ > 4000 mg/kg). Ethanolic extract showed significantly higher potency than the aqueous extract (p = 0.004). At 250 mg/mL, the ethanolic extract (17.67 mm) demonstrated comparable efficacy to fluconazole (18.67 mm, p = 0.355). P. guajava stem bark extracts exhibit promising antifungal properties, with the ethanolic extract showing comparable efficacy to fluconazole at higher concentrations. The extracts are safe at the tested doses and contain diverse bioactive compounds, supporting their ethnomedicinal use in managing oral candidiasis.